2016
DOI: 10.1080/2162402x.2016.1231290
|View full text |Cite
|
Sign up to set email alerts
|

CC-122 immunomodulatory effects in refractory patients with diffuse large B-cell lymphoma

Abstract: In the three patients included in a phase I clinical trial (NCT01421524), we report the immunomodulatory effects and efficacy of CC-122, a novel pleiotropic pathway modifier compound originally developed for broad diffuse large B-cell lymphoma (DLBCL). The chemical structure of CC-122 includes the glutarimide moiety that is known to modulate the immune response. The immunomodulatory agents including lenalidomide represent a promising therapeutic strategy targeting tumors in B-cell lymphoid malignancies. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…CC-122 is a novel immunomodulatory compound containing the conserved glutarimide for CRBN binding. As a derivative of thalidomide, CC-122 has pluripotent activities, including antitumor and modulation of immune cells [37,45]. CC-122 binds CRL4 CRBN E3 ligase to induce the degradation of IKZF1 and IKZF3 in MM cells, diffuse large B-cell lymphoma (DLBCL) cells and xenograft mouse models established from DLBCL cells [36,37].…”
Section: Cc-122 (Avadomide)mentioning
confidence: 99%
“…CC-122 is a novel immunomodulatory compound containing the conserved glutarimide for CRBN binding. As a derivative of thalidomide, CC-122 has pluripotent activities, including antitumor and modulation of immune cells [37,45]. CC-122 binds CRL4 CRBN E3 ligase to induce the degradation of IKZF1 and IKZF3 in MM cells, diffuse large B-cell lymphoma (DLBCL) cells and xenograft mouse models established from DLBCL cells [36,37].…”
Section: Cc-122 (Avadomide)mentioning
confidence: 99%
“…As tumor immunosurveillance in patients with refractory DLBCL has shown diminished natural killer (NK) cell populations and cytotoxic activity, Cubillos-Zapata C et al [35] studied the modulatory and tumorsurveillance effects of CC-122 on the immune system of three DLBCL patients. Their data suggest that CC-122 treatment in DLBCL patients restores the innate immune response after discontinuing therapy.…”
Section: Cc-122mentioning
confidence: 99%
“…Sawas A et al [40] organized a phase 1/2 trial of ublituximab, in patients with relapsed/refractory B-NHL or CLL previously exposed to rituximab. 35 Patients with B-NHL (n = 27) and CLL (n = 8) had a median of 3 prior therapies are enrolled and received treatment of ublituximab. According to their research data ublituximab showed well-tolerated and effective responses in patients with heavily pre-treated.…”
Section: Ublituximabmentioning
confidence: 99%
“…[1][2][3][4][5][6] CC-122 has multiple activities including immune modulation of several immune cell subsets such as T cells, B cells, monocytes, and natural killer cells, antigrowth activity in hepatocellular carcinoma (HCC), antiproliferative activity in multiple tumor types including diffuse large B-cell lymphoma (DLBCL), mantle cell lymphoma, follicular lymphoma (FL), chronic lymphocytic leukemia (CLL), and multiple myeloma (MM) represented by multiple cell lines and antiangiogenic activity as demonstrated by growth factor-induced endothelial cell migration and invasion, inhibition of endothelial cell sprout formation, and hypoxia-inducible factor-1α protein expression in vitro. 1,[7][8][9][10][11] As a result of these pharmacological effects, CC-122 as monotherapy and in combination with other agents is being evaluated as an oncology treatment for hematological malignancies including non-Hodgkin's lymphoma (NHL), FL, DLBCL, MM, and CLL, as well as advanced solid tumors, including glioblastoma multiforme and HCC. 4 In vitro studies showed that CC-122 was metabolized primarily via hydrolysis, oxidation, sulfation, or glucuronidation of the oxidative metabolites and a combination of the pathways.…”
mentioning
confidence: 99%